Regulatory T Cells Increase After rh-MOG Stimulation in Non-Relapsing but Decrease in Relapsing MOG Antibody-Associated Disease at Onset in Children - Horellou, Philippe; de Chalus, Aliénor; Giorgi, Laetitia; Leroy, Carole; Chrétien, Pascale; Hacein-Bey-Abina, Salima; Bourgeois, Christine; Mariette, Xavier; Serguera, Ché; Le Grand, Roger; Deiva, Kumaran (Frontiers in Immunology, 2021)
Background Myelin oligodendrocytes glycoprotein (MOG) antibody-associated disease (MOGAD) represent 25% of pediatric acquired demyelinating syndrome (ADS); 40% of them may relapse, mimicking multiple sclerosis (MS), a recurrent and neurodegenerative ADS, which is MOG-Abs negative. Aims To identify MOG antigenic immunological response differences between MOGAD, MS and control patients, and between relapsing versus non-relapsing subgroups of MOGAD. Methods Three groups of patients were selected: MOGAD (n=12 among which 5 relapsing (MOGR) and 7 non-relapsing (MOGNR)), MS (n=10) and control patients (n=7). Peripheral blood mononuclear cells (PBMC) collected at the time of the first demyelinating event were cultured for 48 h with recombinant human (rh)-MOG protein (10 μg/ml) for a specific stimulation or without stimulation as a negative control. The T cells immunophenotypes were analyzed by flow cytometry. CD4+ T cells, T helper (Th) cells including Th1, Th2, and Th17 were analyzed by intracellular staining of cytokines. Regulatory T cells (Tregs, Foxp3+), CD45RA-Foxp3+ Tregs and subpopulation naive Tregs (CD45RA+Foxp3int), effector Tregs (CD45RA-Foxp3high) and non-suppressive Tregs (CD45RA-Foxp3int) proportions were determined. Results The mean onset age of each group, ranging from 9.9 to 13.8, and sex ratio, were similar between MOGR, MOGNR, MS and control patients as analyzed by one-way ANOVA and Chi-square test. When comparing unstimulated to rh-MOG stimulated T cells, a significant increase in the proportion of Th2 and Th17 cells was observed in MOGAD. Increase of Th17 cells was significant in MOGNR (means: 0.63 ± 0.15 vs. 1.36 ± 0.43; Wilcoxon-test p = 0.03) but not in MOGR. CD4+ Tregs were significantly increased in MOGNR (means: 3.51 ± 0.7 vs. 4.59 ± 1.33; Wilcoxon-test p = 0.046) while they decreased in MOGR. CD45RA-Foxp3+ Tregs were significantly decreased in MOGR (means: 2.37 ± 0.23 vs. 1.99 ± 0.17; paired t-test p = 0.021), but not in MOGNR. MOGR showed the highest ratio of effector Tregs/non suppressive-Tregs, which was significantly higher than in MOGNR. Conclusions Our findings suggest that CD4+ Th2 and Th17 cells are involved in the pathophysiology of MOGAD in children. The opposite response of Tregs to rh-MOG in MOGNR, where CD4+ Tregs increased, and in MOGR, where CD45RA-Foxp3+ Tregs decreased, suggests a probable loss of tolerance toward MOG autoantigen in MOGR which may explain relapses in this recurrent pediatric autoimmune disease.